2015
DOI: 10.1097/bsd.0000000000000266
|View full text |Cite|
|
Sign up to set email alerts
|

Gene Expression Profiling Analysis of Patients With Ankylosing Spondylitis

Abstract: MYH9, BCL11B, PTPRC, CD3G, CD247, CD4, IL7R, and PRF1 might have a correlation with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…While the etiology of AS is unclear, it is thought to be possibly immune-mediated. It has a strong genetic association with the human leukocyte antigen (HLA)-B*27, endopeptidase endoplasmic reticulum aminopeptidase (ERAP1), interleukin-23 receptor (IL23R), IL7R, and caspase recruitment domain-containing protein 9 (CARD9) . The most effective current medication, which basically consists of tumor necrosis factor (TNF-α) or IL-17 inhibitors, seemed to work to arrest bone erosion or syndesmophyte formation.…”
Section: Introductionmentioning
confidence: 99%
“…While the etiology of AS is unclear, it is thought to be possibly immune-mediated. It has a strong genetic association with the human leukocyte antigen (HLA)-B*27, endopeptidase endoplasmic reticulum aminopeptidase (ERAP1), interleukin-23 receptor (IL23R), IL7R, and caspase recruitment domain-containing protein 9 (CARD9) . The most effective current medication, which basically consists of tumor necrosis factor (TNF-α) or IL-17 inhibitors, seemed to work to arrest bone erosion or syndesmophyte formation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Zhao et al ( 8 ) used the same microarray profile of GSE25101 to predict the potential AS-related genes, such as RPL17 , MRPL22 , PSMA6 and PSMA4 . In 2015, also using the same data, Shi et al ( 9 ) identified 284 DEGs correlated with AS (such as MYH9 , BCL11B and CD4 ), and detected the pathway for immune response regulation. Nevertheless, so far, most studies that assessed the genetics of AS focused on a single gene or a single pathway.…”
Section: Introductionmentioning
confidence: 98%